Diseño de un mecanismo para la calificación de crédito que garantice la recuperación de la cartera de la Cooperativa de Ahorro y Crédito General Ángel Flores Ltda. en la ciudad de Quito - Simbaña Cóndor, María José (2015)
The Cooperative Savings and Credit "General Angel Flores" Ltda. it was constituted in 1988, is currently under the control of the Superintendency of Popular and Solidarity Economy. Its market is aimed exclusively at the Armed Forces of Ecuador, offering consumer credit to $ 7,000. This research allows to focus the credit scoring in order to conduct a proper analysis of the borrower and avoid the existence of a credit risk, analyzing the variables that affect and can cause loss liquidity and decline of financial profitability in Cooperative Savings and Credit "General Angel Flores". By designing a credit scoring, the financial institution may have a need to act correctly in managing the loan portfolio and minimize risk in the loan portfolio tool. The credit scoring defines the approval or rejection of a credit application on the basis of economic evaluation of customer data. By setting the applied credit analysis the result of a rating or suggestion of the creditworthiness of the customer is obtained. Finally the design of credit scoring will provide a good basis on which the administrative activities of the Cooperative Savings and Credit "General Angel Flores" will be based, giving a significant contribution that will support management to make timely and positive decisions for the benefit of those who belong to it.